Geometric probability theory and Jaynes’s methodology - Holik, Federico Hernan (2015)
We provide a generalization of the approach to geometric probability advanced by the great mathematician Gian Carlo Rota, in order to apply it to generalized probabilistic physical theories. In particular, we use this generalization to provide an improvement of the Jaynes’ MaxEnt method. The improvement consists in providing a framework for the introduction of symmetry constraints. This allows us to include group theory within MaxEnt. Some examples are provided.